Effect of Polychlorinated Biphenyl Formulations on the Growth of Estuarine Bacteria - Bourquin, Al W. (1975)
Polychlorinated biphenyl formulations inhibited the growth of certain estuarine bacteria. The sensitive strains, although exhibiting some similar physiological characteristics, contained both gram-positive and gram-negative bacteria.